Block Programming Scratch-Based: Interactive Learning Media in the Merdeka Curriculum for Straight Line Equation Material 8th Grade Junior High School - Triayuningtiyas, Alfika; Prasetyo, Puguh Wahyu (Bulletin of Applied Mathematics and Mathematics Education, 2024)
This study aims to develop and produce scratch-based interactive learning media on straight line equation material according to the valid and practical Merdeka Curriculum. This research is motivated by the need for learning media in accordance with the Merdeka Curriculum, to support the learning process on straight line equation material which is considered difficult for students. This development research using the ADDIE model and research was conducted at SMP Muhammadiyah 2 Godean. The research instruments used were interview sheets, material and media expert validation questionnaires, and student response questionnaires. The results shows that the scratch-based learning media developed by researchers were declared valid and practical. The results of the material expert assessment amounted to 95% which met the very valid category. While the media expert's assessment was 73% which met the valid category. The practicality criteria were obtained from the results of student responses to small class trials with a total of 10 students and a large class of 35 students. The small class trial obtained an average score of 87% which meet the criteria for being very practical. Meanwhile, the large class trial obtained an average score of 81% which met the criteria for being very practical.